Phosphorus and acid phosphatase activity in two soils under different use conditions - Fernandes, Luiz Arnaldo; Neto, Antonio Eduardo Furtini; Curi, Nilton; Lima, José Maria de; Guedes, Geraldo Aparecido A. (Pesquisa Agropecuaria Brasileira, 1998)
The experiment was carried out at the greenhouse of Department of Soil Science of Universidade Federal de Lavras, State of Minas Gerais, Brazil, using a Dusky-Red Latosol (Oxisol) and a Structured Dusky-Red Earth (Ultisol), under three use conditions and four practices of correction of soil fertility, with the objective of studying the forms of P in soil, the phosphatase activity and the P extracted by Mehlich 1, Mehlich 3 and resin. Bean plants were cultivated with the objective of correlating the dry matter production with the soil parameters studied. In the Oxisol, independently of use conditions and of practices of fertility correction, it was observed dominance of fraction of P linked to iron, while in the Ultisol higher amounts of P linked to aluminium and calcium were observed. The use conditions had great influence upon organic forms of P and phosphatase activity, being the soils under forest the ones that presented higher amounts of total organic P, organic P in microbial biomass and higher activity of acid and alkaline phosphatases. The three extractants presented positive and significative correlations with the forms of soil inorganic P and with the plant parameters evaluated.